Sosiofotografi Konsep, Desain, hingga Praktik: A Review Essay - Tamba, Wahyu Pratama (Jurnal Sosiologi Reflektif, 2024)
Extract The concept of sociophotography offers an innovative approach to sociology education, particularly at the high school level. By combining photography and sociological theories, this book enables students to connect abstract sociological concepts with real-life social phenomena. It emphasizes active student engagement, where learners document, analyze, and interpret societal issues through photography projects. This approach fosters critical thinking, social awareness, and an appreciation for sociological concepts beyond rote memorization. The book outlines the application of sociophotography through three paradigms: positivistic, interpretative, and critical, each offering distinct methodologies to examine themes such as social equality, cultural change, and urban poverty. These paradigms enrich students' understanding of sociology while developing their practical skills. The book also underscores the pedagogical value of sociophotography in engaging students with sociological materials while stimulating interest in sociology as a discipline. By providing detailed explanations and case studies, it equips educators and students with the tools to explore sociology innovatively. The integration of this method into secondary education curricula can revitalize sociology learning and attract more students to the field. The potential of sociophotography as both an academic and practical tool ensures its relevance in addressing contemporary social challenges, making it a significant contribution to the advancement of sociology education.